Biotransformation of Cyclodextrine-Complexed Semisynthetic Betulin Derivatives by Plant Cells - Häkkinen, Suvi T.; Nygren, Heli; Maiorova, Natalia; Haavikko, Raisa; Alakurtti, Sami; Yli-Kauhaluoma, Jari; Rischer, Heiko; Oksman-Caldentey, Kirsi-Marja (Planta Medica, 2018)
In this study, three semisynthetic betulonic acid-based compounds, 20(29)-dihydrolup-2-en[2,3-d]isoxazol-28-oic acid, 1-betulonoylpyrrolidine, and lupa-2,20(29)-dieno[2,3-b]pyrazin-28-oic acid, were studied in biotransformation experiments using Nicotiana tabacum and Catharanthus roseus cell suspension cultures. Biotransformation was performed using cyclodextrin to aid dissolving poorly water-soluble substrates. Several new derivatives were found, consisting of oxidized and glycosylated (pentose- and hexose-conjugated) products.
Keywords: Nicotiana tabacum; Catharanthus roseus; biotransformation; betulinic acid; Solanaceae; Apocynaceae